2020
DOI: 10.1002/jcsm.12674
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss, malnutrition, and cachexia in COVID‐19: facts and numbers

Abstract: Patients with COVID‐19 disease are prone to develop significant weight loss and clinical cachexia. Three reports with altogether 589 patients that reported on weight loss and cachexia in COVID‐19 were identified. Disease severity of patients and the timing of the assessment during the disease course in these patients were variable—65 patients (11%) were intensive care treated at the time of assessment, and 183 (31%) were cared for in sub‐intensive or intermediate care structures. The frequency of weight loss ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 33 publications
4
98
0
3
Order By: Relevance
“…The deleterious crosstalk between RAGE and RAS might be active also in the muscles of severe COVID-19 patients who develop cachexia [108], a complex metabolic syndrome characterized by the loss of muscle mass and body weight, since both RAGE and RAS signals play crucial roles in inducing muscle protein breakdown [109]. Skeletal muscle tissue expresses a considerable amount of ACE2 [110], making muscles potential targets of SARS-CoV-2.…”
Section: Rage and The Renin-angiotensin System Overlapping Pathways And Biased Signaling With Potential Relevance In Covid-19mentioning
confidence: 99%
“…The deleterious crosstalk between RAGE and RAS might be active also in the muscles of severe COVID-19 patients who develop cachexia [108], a complex metabolic syndrome characterized by the loss of muscle mass and body weight, since both RAGE and RAS signals play crucial roles in inducing muscle protein breakdown [109]. Skeletal muscle tissue expresses a considerable amount of ACE2 [110], making muscles potential targets of SARS-CoV-2.…”
Section: Rage and The Renin-angiotensin System Overlapping Pathways And Biased Signaling With Potential Relevance In Covid-19mentioning
confidence: 99%
“…Hospitalized COVID-19 patients experience many of the factors that define cachexia, including significant weight loss, impaired functional status, loss of appetite, and inflammation [14e16,26]. A recent review of three papers including 589 patients reports 37% of hospitalized COVID-19 patients had cachexia which was correlated with elevated C-reactive protein, impaired renal function, and longer duration of illness [42]. Underweight status (defined as < 18 kg/m 2 ) was reported in only 4% of patients from 7 studies including 6661 patients indicating that initial weight status in this population alone may be insufficient; thus, monitoring of weight loss is important to identify nutritional risk.…”
Section: Prevalence Of Weight Lossmentioning
confidence: 99%
“…The actions of IL-6 on muscle wasting are dose-and time-dependent. Indeed, recent data showed that patients with COVID-19 develop weight loss and cachexia that correlated with high levels of inflammatory parameters (CRP), impaired renal function status, and longer duration of COVID-19 disease [113]. Therefore, the prolonged exposure to high IL-6 in patients with severe COVID-19 may lead to serious muscle wasting, which significantly worsens lung functional capacity and, through the associated negative energy balance, contributes to organ failure, including respiratory failure, as similarly reported in other severe viral infectious diseases [114,115].…”
Section: Interleukin-6 Actions and Immunopathologymentioning
confidence: 99%